Slavery, childhood, and abolition in jamaica 1788-1838 - Vasconcellos, Colleen A. (The University of Georgia Press, 2015)
"This project examines childhood and slavery in Jamaica from 1750, when abolitionist sentiment began to take hold in England, to 1838, when slavery finally ended on the island. By focusing specifically on the changing nature of slave childhood in Jamaica, Vasconcellos examines how childhood and slavery influenced and changed each other throughout this period of study, with the abolitionist movement standing as the main catalyst for change. With each chapter focusing on a different aspect of the slave experience, this monograph explores a childhood that was defined by planter opinion and manipulation, but one that was increasingly affected by the complex processes of slavery, abolition, and eventually emancipation. In doing so, this study reveals a great deal about slave family and childhood from the inside, shining new light on the experiences of slave children and slave families in Jamaica"--Provided by publisher